2012
DOI: 10.1111/j.1461-0248.2012.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic mortality on coral reefs in Caribbean Panama predates coral disease and bleaching

Abstract: Caribbean reef corals have declined precipitously since the 1980s due to regional episodes of bleaching, disease and algal overgrowth, but the extent of earlier degradation due to localised historical disturbances such as land clearing and overfishing remains unresolved. We analysed coral and molluscan fossil assemblages from reefs near Bocas del Toro, Panama to construct a timeline of ecological change from the 19th century-present. We report large changes before 1960 in coastal lagoons coincident with extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 35 publications
(89 reference statements)
4
99
1
2
Order By: Relevance
“…A recent reef coring program conducted at fringing reefs in Bocas' Almirante Bay found a general transition in coral dominance from Porites furcata to Agarica tenuifolia that occurred sometime after 1960 and was unprecedented over a millennial scale (Aronson et al, 2004(Aronson et al, , 2005. The analysis of subfossil coral assemblages excavated from large pits below modern reefs in Bocas confirmed that recent reef deterioration has deeper historical roots: the loss of the regionally co-dominant staghorn coral Acropora cervicornis occurred before 1960 and in some cases likely as far back as the early 1900s in lagoonal reefs, contemporaneous with the onset of land clearing for industrial agriculture (Cramer et al, 2012;Cramer, 2013). This change predated urchin and coral disease and coral bleaching events by at least two decades at lagoonal reefs, confirming the important role of local anthropogenic stressors.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…A recent reef coring program conducted at fringing reefs in Bocas' Almirante Bay found a general transition in coral dominance from Porites furcata to Agarica tenuifolia that occurred sometime after 1960 and was unprecedented over a millennial scale (Aronson et al, 2004(Aronson et al, , 2005. The analysis of subfossil coral assemblages excavated from large pits below modern reefs in Bocas confirmed that recent reef deterioration has deeper historical roots: the loss of the regionally co-dominant staghorn coral Acropora cervicornis occurred before 1960 and in some cases likely as far back as the early 1900s in lagoonal reefs, contemporaneous with the onset of land clearing for industrial agriculture (Cramer et al, 2012;Cramer, 2013). This change predated urchin and coral disease and coral bleaching events by at least two decades at lagoonal reefs, confirming the important role of local anthropogenic stressors.…”
Section: Introductionmentioning
confidence: 61%
“…The dominance of epifaunal suspension feeding bivalves in both environments is indicative of high-productivity coral reef environments dominated by hard substrates and influenced by terrigenous nutrients from river runoff (Birkeland, 1987;Todd et al, 2002). The prevalence of D. frons is a clear indication of the presence of branching colonies of the plexaurid and gorgoniid corals and staghorn coral A. cervicornis that are the primary hosts on which this oyster lives (Forbes, 1971;Cramer et al, 2012). The prevalence of dominant Chama congregata and subdominant C. macerophylla, typically found cemented to (dead) coral or other limestone debris (Jackson, 1972;Harries and Sorauf, 2010), indicates high availability of (live or dead) coral substrate.…”
Section: Bivalvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in coral community structure were still evident nearly 4 y after the hypoxic event, with no apparent recovery in the cover of live coral (P > 0.10). Moreover, these changes occurred in an ecosystem where the coral community had already shifted toward more stress-tolerant species in recent centuries in association with human impacts, including fisheries exploitation and land-use change (30)(31)(32). The long-term effects of hypoxia are potentially different from, and more substantial than, those of other disturbances on coral reefs because hypoxia affects a broad range of taxa including consumers, habitat formers, and pathogens.…”
Section: Significancementioning
confidence: 99%
“…Almirante Bay (figure 1) was flooded sometime before 7.2 ka when modern fringing reefs began to develop [24]. Following the historical and more recent declines of the branching coral Acropora cervicornis [24,25], the fringing reefs of Bocas del Toro became dominated by a mixture of Porites and Agaricia [26].…”
Section: Settingmentioning
confidence: 99%